Bucket-handle uterine rupture during second-trimester medication abortion, a rare form of rupture of the lower uterine segment and vaginal fornix: a case report - Ferid A. Abubeker, MD; Abraham Fessehaye, MD; Mekdes Daba Feyssa, MD,MPH; Sarah Prager, MD,MAS (Elsevier, 2020)
A bucket-handle uterine rupture, a rare form of uterine rupture involving the posterior lower uterine segment and posterior vaginal fornix, occurred in a primigravid woman at 23 weeks of gestation during successful medication abortion.